Elimination of cells with local mismatch in differentiation timing contributes to synchronize tissue development - Maleaume Soulard; Diego Andrés Contreras; Bruno Monier; Thomas Mangeat; Vanessa Dougados; Jennifer Zanet; Francis Corson; Vincent Hakim; François Payre; Anne Pélissier-Monier (iScience)
Summary: During animal development, cells communicate to ensure tissue-wide synchronization of differentiation. While several mechanisms contributing to cell coordination have been described, whether additional mechanisms are at play should cells locally desynchronize remains unknown. Here, we investigate the responses to experimentally induced desynchronized cells during Drosophila epidermis development. We report that cells that behave as if they were “too young” or “too old”, collectively referred to as heterochronous cells, sort out from their normally timed neighbors. Cell sorting is associated with alterations of junctions, cytoskeleton, and cell mechanics. Moreover, local heterochrony ultimately leads to cell elimination. Importantly, we find that some cells naturally undergo either premature or delayed differentiation during development and are similarly eliminated from the tissue. These results show that local imbalance in differentiation timing affects both cell interactions and mechanics, leading to cell sorting, and elimination as a way to correct local heterochrony and safeguard the synchrony of epithelium differentiation.